Pengaruh Kesejahteraan Kerja, Lingkungan Kerja, dan Fasilitas Kerja terhadap Loyalitas Karyawan pada UMKM Konveksi di Klaster Padang Bulan Kota Medan - Sibuea, Nindy Fuzi; Anizar, Anizar; Sembiring, Beby Karina Fawzeea (Lembaga Teewan Journal Solutions, 2026)
This study examines the influence of work well-being, work environment, and work facilities on employee loyalty in micro-scale garment SMEs located in the Padang Bulan cluster, Medan City, where low loyalty is reflected in high turnover and unstable workforce conditions. Using a quantitative explanatory design, data were collected through questionnaires from 80 respondents selected via simple random sampling and analyzed using multiple linear regression. The results reveal that all three variables have a positive and significant effect on employee loyalty, with the work environment emerging as the most dominant factor, underscoring the critical role of social interaction and workplace conditions in shaping employee attachment. Simultaneously, the model explains 42% of the variance in employee loyalty. Furthermore, the findings indicate that employee loyalty remains at a moderate level, characterized by relatively strong engagement and sense of belonging, but weaker long-term retention commitment. These results highlight that employee loyalty in micro-scale SMEs is not solely driven by economic factors but is constructed through an integrated work experience encompassing well-being, relational dynamics, and operational support.